Biological rationale for a patient-specific approach in the treatment of breast cancer. Clinical value of novel biomarkers of breast cancer - R. M. Paltuev (ABV-press, 2019)
Breast cancer, being the most common type of malignant diseases, remains a significant challenge for both clinicians and fundamental researchers. The implementation of screening mammography, as well as adjuvant and neoadjuvant systemic therapy has made a significant progress in tackling the disease. The studies aimed at the assessment of novel biomarkers of breast cancer, alternative to standard ones, are becoming increasingly relevant. A number of new markers, such as p53, CK5/6, SMA, p63, PHH3, E-cadherin, EGFR, FOXA1, androgen receptors, TILs etc., have demonstrated their high predictive and/or prognostic value in multiple studies. New findings suggest that evaluation of novel biomarkers in breast cancer requires further thorough analysis.Recent studies have identified the role of biomarkers in choosing an optimal treatment strategy for breast cancer, estimated the prognostic value of biomarkers associated with tumor proliferative activity (including cyclin D1, G1-cyclin-dependent kinases 4 and 6, and cyclin-dependent kinases 8/19), specified the role of phospho-histone H3 (which is a proliferation marker that can be used to determine tumor grade), and evaluated the prognostic value of androgen receptors and other biomarkers. Multiple studies have also analyzed the expression of various biomarkers and their impact on overall and relapse-free survival.